Impact of cognition, affect, and social factors on technology adoption. (11th September 2019) - AlSaleh, Dhoha; Thakur, Ramendra
In recent decades, high-tech innovations have become very essential in personal and corporate lives and the economy as a whole. The objective of this research is to propose and test a new model for consumer acceptance of technology by including three social constructs: social influence, susceptibility to normative influence, and susceptibility to informational influence. The new proposed model is expected to significantly improve the prediction of intentions to adopt high-tech products compared to the TAM and CAT models. 11 hypotheses were tested in this study using SEM. Results showcase that cognition (perceived usefulness) and affect (pleasure, arousal, and dominance) influences consumers' attitude. Furthermore, this research also suggests that social factor (social influence) also has a significant effect on attitude toward adopting technology innovations. Overall, results indicate that incorporation of cognition, affect, and social factors into a model enhances the explanatory power of the model.